COVID-19, State of the Adult and Pediatric Heart: From Myocardial Injury to Cardiac Effect of Potential Therapeutic Intervention - Iacobazzi, Dominga; Baquedano, Mai; Madeddu, Paolo; Caputo, Massimo (Frontiers in Cardiovascular Medicine, 2020)
While the COVID-19 pandemic keeps spreading rapidly, resulting into considerable morbidity and mortality worldwide, multiple efforts are being made by the international scientific community to understand the pathogenesis of the viral infection and its clinical outcome. Older age and comorbidities have consistently been reported as risk factors for unfavourable prognosis, with cardiovascular disease accounting for up to the 10 % of comorbid conditions among the infected patients. Understanding of the mechanism underlying the effect of this infection on patients with cardiovascular disease is essential to manage and improve clinical strategies against the disease in such population. In this review, we summarise the impact of COVID-19 on patients with underlying cardiovascular conditions, and the cardiac implication of known and emerging therapeutic strategies. Our future effort will aim further elucidate how the type and severity of the cardiac disease, with particular regard to Congenital Heart Disease, influences the prognosis and the outcome of the viral infection.